Increased expression of the long non-coding RNA ANRIL promotes lung cancer cell metastasis and correlates with poor prognosis - Lin, Ling (Diagn Pathol, 2015)
BACKGROUND: Emerging evidences indicate that dysregulated long non-coding RNAs (lncRNAs) are implicated in cancer tumorigenesis and progression. LncRNA ANRIL has been shown to promote the progression of gastric cancer. However, the role of lncRNA ANRIL in human non-small cell lung cancer (NSCLC) remains unclear. METHODS: Expression of lncRNA ANRIL was analyzed in 87 NSCLC tissues and three lung cancer cell lines by quantitative real-time PCR (qRT-PCR). The correlation of lncRNA ANRIL with clinicopathological features and prognosis was analyzed. Suppression of lncRNA ANRIL using siRNA treatment was performed in order to explore its role in tumor progression. RESULTS: The expression level of lncRNA ANRIL was higher in NSCLC tissues and lung cancer cells than in adjacent non-tumor tissues and normal human bronchial epithelial cells. Higher expression of lncRNA ANRIL in NSCLC tissues was associated with higher TNM stage and advanced lymph node metastasis. Patients with high lncRNA ANRIL expression had poorer overall survival compared with low lncRNA ANRIL group. Univariate and multivariate analyses suggested that high expression of lncRNA ANRIL was an independent poor prognostic indicator for NSCLC patients. Moreover, knockdown of lncRNA ANRIL expression could inhibit lung cancer cell proliferation, migration and invasion in vitro. CONCLUSIONS: Our results suggested that lncRNA ANRIL was a potential biomarker for NSCLC prognosis, and the dysregulation of lncRNA ANRIL may play an important role in NSCLC progression. VIRTUAL SLIDES: The virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/1707061287149690.